Pencabutan Izin Usaha oleh Presiden sebagai Instrumen Penegakan Hukum Lingkungan: Analisis Yuridis Kebijakan Penertiban Kawasan Hutan - Putri Debora Silalahi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The revocation of business licenses by the President of the Republic of Indonesia against 28 companies proven to have violated forest utilization regulations signifies a shift in environmental law enforcement from a predominantly punitive criminal approach to preventive administrative measures. This article aims to analyze the legal basis of the President’s authority to revoke business licenses related to natural resource utilization, to position license revocation as an instrument of environmental law enforcement within Indonesia’s legal system, and to assess its implications for environmental protection and legal certainty for business actors. This study employs a normative juridical research method using statutory and conceptual approaches. The findings indicate that Presidential license revocation possesses juridical legitimacy within the framework of the rule of law and environmental and forestry legislation. Nevertheless, the implementation of such a policy requires clear administrative procedural standards to ensure legal certainty and to prevent potential abuse of power. This article concludes that license revocation can function as an effective environmental law enforcement instrument provided that it is accompanied by adequate oversight mechanisms and due process of law.